2014
DOI: 10.1177/1357633x14555620
|View full text |Cite
|
Sign up to set email alerts
|

Trial of telemedicine for patients on home ventilator support: feasibility, confidence in clinical management and use in medical decision-making

Abstract: We investigated whether telemedicine (videoconferencing) was feasible in patients with special care needs on home ventilation, whether it affected the confidence of families about the clinical management of their child, and whether it supported clinical decision-making. Videoconferencing software was provided free for 14 families who had a computer and webcam. Families completed questionnaires about clinical management before the addition of telemedicine and 2-3 months after they had used telemedicine. They al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 12 publications
0
41
0
Order By: Relevance
“…The risk of hospitalisation was also lower in the videoconferencing group . Videoconferencing has also been shown to be feasible in the management of children on home ventilator support as well as for paediatric palliative care at home .…”
Section: Introductionmentioning
confidence: 90%
“…The risk of hospitalisation was also lower in the videoconferencing group . Videoconferencing has also been shown to be feasible in the management of children on home ventilator support as well as for paediatric palliative care at home .…”
Section: Introductionmentioning
confidence: 90%
“…74,75 A recent small pilot study from Boston Children's Hospital in the US enrolled 14 patients followed by telemedicine, of whom nine were children on HMV (invasive and noninvasive). 70 The study showed a high degree of acceptance by the families and felt that the use of telemedicine avoided clinic and emergency room visits.…”
Section: Telemedicinementioning
confidence: 90%
“…We could not identify strong evidence on the use of telemedicine for follow-up care of children on HMV. Only three publications reported the telemedicine experience in such children [68][69][70] Even in adults, evidence is scarce. There were two systematic reviews on telemedicine that provided some important conclusions; one was solely on patients with diabetes 71 and the other presented data on four conditions, including pulmonary conditions.…”
Section: Telemedicinementioning
confidence: 99%
“…These patients and their families often experience high levels of isolation, fears about functional decline and death, diminishing quality of life as well as depression, concerns about caregivers, financial worries, and day‐to‐day stressors associated with challenging medical regimens. Furthermore, mobile‐based telemedicine may decrease risks associated with travel (eg, infection control risks, discomfort) in critically ill populations, such as patients with amyotrophic lateral sclerosis (ALS) 28 and children on ventilators 29 . Home‐based telemedicine addresses challenges in driving associated with vision loss, seizures, cognitive difficulties, and other conditions.…”
mentioning
confidence: 99%